Filariasis infection is a probable cause of implantation failure in in vitro fertilization cycles - Bazi, Tony (2006)
Objective To describe a parasitic infection that probably affected the implantation of good-quality embryos in an in vitro fertilization (IVF) cycle. Design Case report. Setting Tertiary care center in a university hospital. Patient(s) A 36-year-old Caucasian female with primary unexplained infertility. The patient underwent two cycles of IVF with good-quality embryos transferred; however, no pregnancy ensued despite adequate luteal support. Intervention(s) In vitro fertilization cycles, CBC, blood smear, evaluation for eosinophilia including serological evaluation for parasitic infections. Main Outcome Measure(s) Pregnancy. Result(s) Following treatment for filariasis, a repeat IVF cycle using the same stimulation protocol yielded a full-term pregnancy. Conclusion(s) This case is of particular importance because, to our knowledge, it is the first to describe a parasitic infection that probably affected the implantation of good-quality embryos in IVF cycles.